The role of emotion and emotion regulation in job stress and well being - Perrewé, Pamela L.; Halbesleben, Jonathon R. B.; Rosen, Christopher C. (Emerald, 2013)
This series promotes theory and research in the growing area of occupational stress, health and well being, and in the process, showcases the work of the best researchers and theorists who contribute to this area. Furthermore, the series promotes the development of truly path-breaking contributions that significantly advance theory and provide specific directions for future work. Each volume of this series has a specific theme and provides a rich compilation of the insights of the top researchers from a variety of fields concerning what we know about work stress and well being and what the critical gaps are that most need attention for the field to progress. The theme for volume 11 concerns the role of emotion and emotion regulation in job stress and well-being.
Includes index.
Keywords: Job stress.; Emotions.; elektronické knihy; electronic books